Peran Efikasi Diri, Pelatihan Karyawan, dan Pengembangan SDM dalam Meningkatkan Kinerja Karyawan - Widya Rahayuningsih (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The role of job training, self-efficacy, and human resource development (HRD) in improving employee performance is discussed in this study. The problem raised is how these three components can synergistically influence employee work efficiency, considering the many challenges faced by organizations in optimizing their human resource potential. The library method and literature review approach are used in this study. This involves the analysis of primary and secondary data from reliable international journals indexed by Scopus and national journals indexed by Shinta. These data were collected through a review of relevant literature covering theories and empirical research on self-efficacy, job training, HRD, and their effects on performance. The results of the study indicate that increasing employee motivation and confidence to complete assigned tasks is very important. Technical skills and adaptability to changes in the work environment are improved through competency-based job training. Meanwhile, an innovative and productive work culture is generated through continuous learning and mentoring programs. When used together, these three components can contribute to improving individual and organizational performance. According to this study, to maintain the sustainability and competitiveness of organizations in the modern era, a holistic approach to HR management is essential